How to Improve Students' Analytical Ability: Using Sparkol Videoscribe Assisted by PhET Simulation - Siti Rofikoh; Siska Desy Fatmaryanti; Sriyono Sriyono (Radiasi : Jurnal Berkala Pendidikan Fisika, 2021)
The Covid-19 pandemic caused the learning process to carried out online, and to improve students' analytical skills, it was necessary to have supporting media in the online learning process. So that this study aims to determine the feasibility of physics learning media using Sparkol Videoscribe assisted by PhET simulation to improve students' analytical skills in terms of the validity, practicality, and effectiveness of the media developed. This study uses the ADDIE research model, namely analysis, design, development, implementation, and evaluation. The subject of this research is the students of class X MIPA MA Syamsul Huda Kedungreja. Data collection techniques used are validation sheets, student response questionnaires, observation sheets, and learning outcomes tests. The results of this study indicate that: (1) the validation results obtained from the validator expert get a value of 3.84 by material experts and 3.85 by media experts include a very good category, so it can be said to be valid, (2) physics learning media using Sparkol Vvideoscribe is practical because it can be carried out in limited trials and broad trials well, and gets a positive response from students, (3) the results of the analytical ability test increase learning outcomes with an N-gain of 0.71 including the category high, so it is declared effective. Thus the physics learning media using sparkol videoscribe assisted by PhET simulation in this study is declared valid, practical, and effective so that it is feasible to use it to improve students' analytical skills